“WE ARE AZOREAN”: DISCOURSES AND PRACTICES OF FOLK CULTURE IN SANTA CATARINA (BRAZIL) - João Leal (Etnográfica, 2005)
The development of the Azoreanist movement is a major feature in the contemporary cultural and political scene of the state of Santa Catarina (southern Brazil). Aimed at the rediscovery and celebration of the Azorean roots of the island of Santa Catarina and other coastal areas of the state, the Azoreanist movement dates back to the 1940s and, having remained an elite endeavor for several decades, recently became a very influential movement. This paper seeks to investigate the prominent role played by folk culture in the activities and identity claims of the movement, contrasting its ethnogenealogical thematicizations on Santa Catarina’s folk culture with more “autochthonous” visions of local folklore.